Growth Performance, Feed Utilization Efficiency, and Physiological Responses of Broiler Chickens Supplemented with Ethanolic Turmeric (Curcuma Longa L.) Extract in Drinking Water - Cabbab, Jurwin; Mangoba, Alford Glenn; Marcos, Mark Joker; Nicolas, Karina Marie; Gaffud, Oliva; Reyes, Joel; Temanel, Florenda (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the effects of varying levels of ethanolic turmeric (Curcuma longa) extract administered through drinking water on the growth performance, feed utilization, and water consumption of broiler chickens and assessed its potential as a natural growth-promoting additive. Anchored on the concept that the bioactive compounds of turmeric enhance digestion, nutrient utilization, antioxidant activity, and immune function, the study employed an experimental research design using a Completely Randomized Design (CRD). A total of 150 one-day-old Cobb 500 broiler chicks were randomly assigned to five treatment groups with three replications. Ethanolic turmeric extract was prepared through maceration and administered at concentrations of 0, 5, 10, 15, and 20 g/L in drinking water. Data on body weight, weight gain, percentage rate of growth, feed consumption, feed conversion ratio, feed conversion efficiency, and water consumption were analyzed using Analysis of Variance (ANOVA), with treatment means compared through the Honestly Significant Difference (HSD) test. The results showed no significant differences in most growth performance, feed utilization, and water consumption parameters. However, broilers supplemented with 15 g/L turmeric extract attained the highest final body weight, while the 5 g/L treatment achieved the best feed conversion ratio and greatest economic return. The findings indicate that moderate levels of turmeric extract, particularly 5–15 g/L, can improve selected production traits and may serve as a natural growth-promoting additive in broiler production. The study supports Sustainable Development Goal (SDG) 2: Zero Hunger by promoting sustainable livestock production and SDG 8: Decent Work and Economic Growth by identifying a natural feed additive that may improve production efficiency and economic returns. Its findings contribute to agricultural and economic sustainability by encouraging safer and more efficient poultry production practices.